Optimize your greatest asset--your people : how to apply analytics to big data to improve your human capital investments - Pease, Gene, 1950- (Business professional collection, 2015)
Packed with practical examples and case studies, this detailed guide brings advanced analytics into Human Resources, giving you a framework for optimizing human capital investments through predictive analysis. --